KADAR KLORIN PADA ES BATU DI JALAN PROF DR SOEPOMO KOTA YOGYAKARTA - Muchsin Maulana; Septian Emma Dwi Jatmika; Subhan Zul Ardi; Eka Putri Hartuti (Universitas Ahmad Dahlan, 2022)
Water is one of the necessities of life and is the basis for life on earth. Water can be in the form of solids, liquids, and gases. Ice cubes are a food product that is well known to the general public and is considered safe for consumption. But prone to contain chlorine. The presence of chlorine in water is considered to have a high correlation to cause diseases, one of which is bladder cancer. Determine the content of chlorine levels in ice cubes required laboratory examination. The purpose of the study was to determine the level of chlorine in ice cubes on Jalan Prof. Dr. Soepomo, Yogyakarta City. The type of research is descriptive qualitative. Taking 30 samples of ice cubes from beverage traders then conducting laboratory tests to identify the phenomena and characteristics that exist in ice cubes and conducting interviews with 5 representatives of beverage traders to strengthen laboratory results. The results of the analysis showed that the chlorine content in ice cubes from thirty samples taken from Jalan Prof. Dr. Soepomo Yogyakarta City was <0.03 mg/L. All of them are under the standard of the Regulation of the Minister of Health of the Republic of Indonesia Number 492/MENKES/PER/IV/2010 concerning the requirements for the quality of clean water or drinking water that has been set at 0.2-0.5 mg/L. The results of the interview that the source of water used by the ice cube maker is direct PDAM water and refilled water. The water is directly processed in ice cube packs without going through the first procprocessanwhile, the source of mineral water refills for ice cube makers first buys refilled water that is ready for consumption. This will make the ice cubes not free from disease and bacteria contained in the ice cubes. There is a chlorine content of < 0.03 mh/L in ice cubes on Jalan Prof. Dr. Soepomo, Yogyakarta City.